Working to Learn, Learning to Work: a narrative inquiry into the well-being of an international PhD student in Taiwan - Mohammad Romadhoni (Journal of Teacher Well-being, 2025)
International doctoral students often face complex challenges related to academic responsibilities, financial pressures, and adapting to new cultures, especially those from developing countries seeking upward mobility and long-term stability. This study explores the experiences of an Indonesian PhD student in Taiwan who, while enrolled in two simultaneous doctoral programs, also works as an English teacher and research assistant. The goal is to understand how international doctoral students shape their well-being and academic identity while managing multiple roles. Using narrative inquiry as the chosen method, this research analyzes autobiographical reflections. It uses thematic narrative analysis to examine how the participant interprets and finds meaning in his experiences across academic, professional, and emotional areas. The results show that employment serves both as an economic strategy and a professional growth opportunity, strengthening the participant’s academic identity. Despite the challenges of a heavy academic workload and adjusting to a new culture, the participant finds support mainly from his spouse and his personal ambitions. His well-being is seen not as a static state but as a dynamic process influenced by resilience, meaning-making, and long-term goals. The study concludes that the well-being of international doctoral students is actively shaped through the negotiation of their identities, responsibilities, and opportunities during a transnational academic journey.